After The War Is Over, Truth and Reconciliation?: Impressions and Reflections - Bloom, Len (PINS-Psychology in Society, 2026)
Seven months after the collapse of Nazi Germany, the Nuremberg trials of Nazi leaders and officials opened. In 1993, one of the first Acts of the South African transitional government set up a Truth and Reconciliation Commission (TRC). It was charged by the Act to provide for the investigation and establishment of as complete a picture as possible of all gross violations of human rights committed during the period March 1960 to December 1993, and emanating from the conflicts of the past. Both the TRC and the Nuremberg tribunals were concerned with crimes against humanity. Both, implicitly, faced the problems of bringing sanity to insane societies, by enabling a reluctant society to face its past. In this article, I consider some of the emotional and social issues that I believe are still unsettled and that influence social and individual life in South Africa. Some of these issues are symbolised by the relationships seen in the workings of the TRC, in which such problems as unmasking myths, mourning and ending relationships often influenced what was going on at the hearings, just as they do in wider social life.